Impact of preoperative BRCA1/2 testing on surgical decision making in patients with newly diagnosed breast cancer. Issue 4 (2nd March 2018) - Yadav, Siddhartha; Jinna, Sruthi; Pereira‐Rodrigues, Otavio; Reeves, Ashley; Campian, Sarah; Sufka, Amy; Zakalik, Dana
Abstract: The utility and benefit of integrating germ‐line genetic testing into the management of newly diagnosed breast cancer is not fully understood. This study evaluates the impact of preoperative genetic testing on surgical decision making in patients with newly diagnosed breast cancer. Women with newly diagnosed breast cancer were classified into preoperative or postoperative genetic testing group, depending on whether they received their genetic testing results prior to or after their first surgery. Demographics, tumor characteristics, surgical treatment, and results of genetic testing were retrospectively collected. A total of 997 patients were evaluated, 531 (53.3%) in the preoperative genetic testing group and 466 (46.7%) in the postoperative group. Majority (87.2%) of BRCA ‐positive women in the preoperative group underwent bilateral mastectomy as first surgery. Majority (70.6%) of BRCA ‐positive women in postoperative group underwent partial mastectomy as first surgery prior to receiving their genetic testing result. Nearly half (41.2%) of these women in the postoperative group with partial mastectomy underwent bilateral mastectomy after receiving their BRCA ‐positive result. Time from diagnosis to first surgery was longer in the preoperative genetic testing group. Younger age, bilateral cancer, BRCA1/2 ‐positive results, and preoperative genetic testing were significant predictors of bilateral mastectomy at first surgery. Preoperative genetic testing impacts initial surgical treatment in BRCA1/2 ‐positive patients and reduces the need for additional surgeries.